Analysis of Influence of Islamic Revival in Central Asia States of Safety in Xinjiang China - Meng Xiangyun (Проблемы постсоветского пространства, 2018)
After the Arabs invaded Central Asia, Islam began to dominate the region. Although during the Soviet Union due to socialist ideology Islam in the region was diluted, after the independence of the five Central Asian countries, Islam still met with the revival. Especially in the 1980s, some Islamic groups in Central Asia began to pay close attention to the Islamic revolution in Iran and the jihad in Afghanistan, the ideas of radicalism under Islamic slogans also began to penetrate. In fact, during the Soviet era, Islam was still generally considered by the people as a way of moral recovery of society. In the mind, morality and Islam have almost always been identified. This article examines the resurgence of Islam in Central Asia after the collapse of the Soviet Union and the spread of extremist Islamic ideas in the region, analyzes the impact of the Islamic renaissance in Central Asia on Xinjiang China, especially the influence of the extremist organization Hizb ut-Tahrir on the activities of Chinese "three forces of evil" and cross-border crimes, arms smuggling and drug trafficking. The author believes that although the Islamic revival movement in different countries had a great influence on the development of Islamic fundamentalism (IF) and even extremist ideology in China, the Islamic revival movement in Central Asia had a more direct impact on the security situation in Xinjiang. Therefore, the Xinjiang local government in recent years has strengthened control and surveillance at the border of China and Central Asia and is carrying out a number of measures to control the area, aimed at preventing the spread of extreme ideas and terrorist activities. Although now the main part of the IF was defeated, judging by the prevailing situation, the security situation in the Fergana region of Central Asia, which is located on the border of Uzbekistan, Kyrgyzstan and Tajikistan, is still the most serious in the future. The development of remnants and branches in Central Asia and their threat to China's security are still underestimated.